Avances en el tratamiento del accidente cerebrovascular isquémico - Manterola V., José Luis; Díaz T., Violeta (Revista Hospital Clínico Universidad de Chile, 2009)
Stroke is a devastating disease with a high mortality and high degree of disability. In the nineties a new specific treatment was proved to be beneficial, the intravenous recombinant tisular plasminogen activator (IV r-TPA). The first notion of pharmacologic vessel revascularization marked a new era in stroke treatment. However, there are cases that need a more aggressive approach, such as large intracranial vessel occlusion. Recently, new endovascular approaches and an explosive development of devices to remove or suck the thrombus, bring a second revolution in the manner that we treat stroke.